Elaborating Cultural Meanings behind the Use of Metaphors in Javanese Traditional Songs - Saadiah, Nur Khofifah (Research Community for Critical Society and Environment, 2025)
Language style is the beauty of language. Many literary works, in the form of poetry, rhymes, and other genres, including songs, use language styles to beautify word arrangement and convey meaning, as in traditional Javanese songs. However, limited understanding of metaphorical language in Javanese songs, particularly those used in Islamic da'wah, hinders insight into their cultural significance and the depth of their messages, necessitating an in-depth analysis of selected works to uncover the layers of meaning conveyed by these metaphors. As in this research, the analysis of metaphorical language styles is discussed in depth by limiting the number of songs analyzed. Researchers analyzed five selected songs, which are Javanese cultural heritage, that Sunan Kalijaga and Sunan Giri popularized as a form of Islamic da'wah' preaching'. The songs analyzed in this study include Kidung Wahyu Kalaseba, Padang Mbulan, Lir Ilir, Cublak-cublak Suweng, and Gambang Suling—analysis of Michael C. Halley's version of the metaphor used in this study. The researcher used descriptive qualitative analysis to complete the discussion by collecting the lyrics of the song being analyzed, examining their meaning, drawing on several literature reviews from previous studies, and analyzing the meaning. The results of this research show that there are four Being metaphors, three Substance metaphors, two Cosmos metaphors, two Human metaphors, one Animate metaphor, two Living metaphors, one Terrestrial metaphor, one Object metaphor, and one Energetic metaphor.